2018
DOI: 10.1371/journal.pcbi.1006229
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter oligomerization involves the scaffold domain, but spares the bundle domain

Abstract: The human dopamine transporter (hDAT) is located on presynaptic neurons, where it plays an essential role in limiting dopaminergic signaling by temporarily curtailing high neurotransmitter concentration through rapid re-uptake. Transport by hDAT is energized by transmembrane ionic gradients. Dysfunction of this transporter leads to disease states, such as Parkinson’s disease, bipolar disorder or depression. It has been shown that hDAT and other members of the monoamine transporter family exist in oligomeric fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 79 publications
2
30
0
Order By: Relevance
“…Oligomers could also have deleterious effects on cells as observed in the case of neurodegenerative disorders (1214). For a large number of proteins, there are specific binding domains that facilitate or modulate oligomerization (15, 16). Lipids have also been found to be important in membrane protein folding and oligomerization (1719).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligomers could also have deleterious effects on cells as observed in the case of neurodegenerative disorders (1214). For a large number of proteins, there are specific binding domains that facilitate or modulate oligomerization (15, 16). Lipids have also been found to be important in membrane protein folding and oligomerization (1719).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cross-linking experiments suggest the involvement of TMHs 4 and 6 in the interfaces of symmetrical hDAT dimers (31, 35, 36). More recently, unbiased molecular dynamics simulations followed the dimerization of two randomly oriented hDAT monomers and reported the existence of a limited number of symmetric and asymmetric dimers (16). Additionally, the bundle domain comprising of TMHs 1, 2, 6, and 7 was largely excluded from the dimer interface, whereas the scaffold domain formed a significant part of the dimer interface (16).…”
Section: Introductionmentioning
confidence: 99%
“…This is a little surprising given that TMH6, together with 1, 2 and 7, forms part of the so-called bundle domain responsible for transport. A more recent analysis suggested that DAT forms a range of different dimer interfaces involving virtually all the protein surface, except the vast majority of TMHs 1, 2, 6 and 7 (Figure 2A,B) [29]. The authors of this more recent study do not rule out a dimer interface involving the intermolecular disulfide bridge mentioned above; however, if a covalent interaction was involved in mediating the interactions between individual protomers, this should be captured in the crystal structure.…”
Section: The Neurotransmitter–sodium Symporter Family Of Transportersmentioning
confidence: 99%
“…( B ) DAT monomer coloured and labelled as in ( A ) and shown from the extracellular side of the membrane. The black curve indicates all the regions predicted to be able form DAT:DAT interactions by MD simulations [29]. ( C ) LeuT dimer (PDB: 3TT1 [31]) looking through the membrane.…”
Section: The Neurotransmitter–sodium Symporter Family Of Transportersmentioning
confidence: 99%
See 1 more Smart Citation